Vitamin D Treatment Effect on Serum Endocan and High-Sensitivity C-Reactive Protein Levels in Renal Transplant Patients. (December 2016) - Atis, Omer; Keles, Mustafa; Cankaya, Erdem; Dogan, Hasan; Aksoy, Hulya; Akcay, Fatih
Context: Endocan is a marker showing endothelial dysfunction and inflammation. Significantly increased endocan levels have been observed in serum of patients with sepsis and cancer. Objective: Our aim was to investigate the relationship between vitamin D treatment and serum endocan and high-sensitivity C-reactive protein (hs-CRP) levels as inflammatory markers in transplant patients. Design: Prospective. Setting: Nephrology clinic. Patients: Thirty-eight renal transplant patients with serum 25-hydroxy-vitamin D (25-OH-vitamin D) levels below 20 ng/mL and transplanted at least 12 months. Intervention: One-time oral dose of 300 000 IU vitamin D3. Main Outcome Measures: Before and after vitamin D treatment, serum endocan, hs-CRP, calcium, phosphorus, and parathyroid hormone (PTH) levels were measured. Results: Median serum endocan and PTH values before vitamin D were significantly higher than those of after treatment values ( P = .001 and P < .001, respectively). On the other hand, serum total calcium and phosphorus levels before vitamin D treatment were lower than the values obtained after vitamin D treatment ( P = .0013 and P < .001, respectively). Serum hs-CRP was lower after vitamin D therapy than before, but the difference was not statistically significant ( P = .06). A moderate negative correlation was determined between endocan and 25-OH-vitamin D levels after treatment with vitamin D ( r = −.36, P = .02). Conclusion: This study has revealed that vitamin D treatment reduced markers of endothelial dysfunction in patients with renal transplantation and vitamin D deficiency.